Fatigue life prediction of clutch sleeve based on abrasion mathematical model in service period. Issue 3 (10th September 2019) - Liu, Xintian; Kan, Fuchao; Wang, Haijie; Xin, Xiufeng; Wang, Zhaoqiang; Huang, Hu
Abstract: To predict the service life of clutch sleeve, major reasons for the change of clearance between the clutch sleeve and shell in service period are analysed. A mathematical model of the clearance is established considering abrasion of the step outside sleeve caused by friction. To determine the size of abrasion, a micro‐convex body model for the friction surface is built. Based on surface fatigue abrasion theory, an abrasion model is established. A life model is established based on the entire abrasion of the sleeve. Fatigue life of sleeve is predicted using the model based on actual surface morphology parameters of the enterprise products. Major factors affecting the abrasion speed are discussed and determined after the prediction result is analysed.